Behavioral Characteristics of Older Adults in Community Public Spaces: Gender and Aging in Dalian, China. (August 2021) - Yu, Wenting; Zhou, Bo; Liu, Jianjun
As people age, the community gradually becomes the main place for their daily activities. In old residential communities in China, variations in behaviors and venue choices of older adults reflect gender differences. This study focuses on the behavioral gender differences in old residential communities and the characteristics of venue use under the influence of the unique policies and culture of China. Semistructured interviews, behavioral mapping, and photo recording were utilized for data collection. The results showed that gender differences were reflected in the variability of behaviors and venue use of older adults. These differences are due to people's living habits and gender characteristics as well as the top–down development of feminism in China. This study highlights the important role played by policies and culture in behavioral differences and stresses that systematically environmental construction could be used as a balanced means to address gender differences in old residential communities. This study also suggests minimizing activities with a strong gender orientation, balancing the gender allocation of service staff for older adults, and emphasizing space flexibility and versatility could help achieve a gender-balanced community environment.